(untitled) (World Bulletin of Public Health, 2025)
The problem of patient adherence to therapy is multifaceted. In general, three main reasons for poor adherence have been identified. Blood pressure in everyday life: physician inertia, low patient adherence to treatment, and challenges in healthcare systems’ approaches to chronic care. Finding ways to improve the effectiveness of treatment for patients with cardiovascular disease remains a pressing issue in modern healthcare. The diversity of diseases requiring long-term medication adherence, the heterogeneity of patient groups in real-life outpatient settings, and the lack of sufficient methodological programs for assessing adherence to therapy prompt the search for new ways to organize a system for assessing and supporting patient adherence to treatment in long-term outpatient settings. The need to optimize the long-term treatment of patients with hypertension in outpatient settings and the need for a comprehensive application of methods for identifying and improving poor adherence to therapy in real-life outpatient settings motivated this research